Colonization ability as an indicator of enhanced biocontrol capacity—An example using two Bacillus amyloliquefaciens strains and Botrytis cinerea infection of tomatoes. Issue 9 (15th June 2018) - Salvatierra‐Martinez, Ricardo; Arancibia, Williams; Araya, Michael; Aguilera, Selene; Olalde, Víctor; Bravo, Jaime; Stoll, Alexandra
Abstract: An understanding of biocontrol activities is important when developing microorganism‐based alternatives to conventional fungicides. From our bacterial collection, we selected two strains (BBC023 and BBC047) for their outstanding antagonistic capacity against fungal phytopathogens and growth‐promoting abilities towards Arabidopsis thaliana . According to physiological and molecular characterizations, both strains were classified as Bacillus amyloliquefaciens and were tested against Botrytis cinerea in vitro and in a tomato. Both strains secrete lipopeptide‐like compounds that contribute to their in vitro antagonism. SEM‐images showed altered B. cinerea mycelial structures that were consistent with previous reports of the direct action of lipopeptides against fungal hyphae. The strains were applied to the roots (R), leaves (foliar ‐ F) or root/leaves (R/F) on tomato plants. All treatments significantly reduced the severity of B. cinerea infection (measured as a control index). However, only root applications (R and R/F) led to growth promotion in the tomato plants. We detected the production of indole acetic acid (IAA) and 2, 3‐butanediol as growth promotion traits in the two strains. For both strains, the R/F treatment showed the highest control index, suggesting a synergic effect of direct antagonism against B. cinerea and resistance induction in the plant. In addition, in vitro antagonism of BBC023 and BBC047 against B. cinerea was similar; whereas in the F application, strain BBC047 significantly improved plant resistance and maintained a higher population density over time on tomato leaves, compared to BBC023. BBC047 was also able to produce a complex and robust biofilm in Msgg medium compared with that of BBC023. We linked the reduced biocontrol of BBC023 on leaves with its limited ability to generate robust biofilms and colonize the phylloplane. At last, we highlight the potential of the native Bacillus strains as promising alternatives for the development of bioproducts for sustainable agriculture.